Structural behaviour of a masonry wall under cyclic load: experimental and numerical study - Alexandre Costa (2006)
This paper presents a numerical and experimental study on the structural behaviour of a stone masonry wall recovered from a house in Faial island, Archipelago of Azores, that collapsed during the 9th July 1998 earthquake. The wall was identified and tested under cyclic horizontal loads at the Laboratory of Seismic and Structural Engineering (LESE) of the Faculty of Engineering of Porto University, to simulate the effects of a horizontal seismic action. In particular, the experimental response allowed accessing the cyclic behaviour and estimation of energy dissipation and ductility capacity of the structure, as well as its strength and stiffness. Afterwards the wall was simulated numerically using a finite element method. The stones and the infill were simulated separately using different behaviour models and the link between the two materials was simulated with joint elements (Pegon, 1999). Finally, the numerical results were compared to the experimental response.